NILAI-NILAI PENDIDIKAN ISLAM DALAM TRADISI MENDAK DI KELURAHAN AIR BANG KECAMATAN CURUP TENGAH KABUPATEN REJANG LEBONG - apriyansyah, apriansyah; ningsih, dwi ria; ifnaldi, ifnaldi; Apriani, eka (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2024)
Air Bang sub-district is one of the sub-districts in Rejang Lebong district, where the majority of people are Javanese. The Javanese tribe is a tribe that upholds existing traditions, one of which is the annual tradition of deceased people called the mendak tradition. This research aims to find out what values ​​of Islamic education are contained in the mendak tradition carried out by the Javanese community in the Air Bang sub-district. . Therefore, this needs to be studied to find out what values ​​of Islamic education are contained in the Mendak tradition through a series of Mendak traditional processions in the sub-district. The research approach used to study this matter is a qualitative approach and the type of research used is ethnography. Data in the form of words is taken from informants or respondents when they are interviewed, while additional data is in the form of documents. In the process of collecting data, researchers used three methods, namely the observation method, interview method and documentation method. Then the researcher used data analysis techniques through 3 three stages, namely data reduction, data presentation, and verification of conclusions. The results of research on the Values ​​of Islamic Education in the Mendak Tradition in Air Bang Village, Curup Tengah District, Rejang Lebong Regency show that first, in the procession of implementing the Mendak tradition in Air Bang Village there are several stages, namely: opening, host's remarks, yasin reading, reading. tahlil and prayer. Second, the values ​​of Islamic education in the Mendak tradition in the Air Bang sub-district, namely the moral values ​​towards Allah found in the recitation of yasin, tahlil and prayers, morals towards humans and fellow humans found in mutual help and mutual cooperation activities to prepare for the peak night of the Mendak tradition.